2019
DOI: 10.1177/1049732319844999
|View full text |Cite
|
Sign up to set email alerts
|

Patient Self-worth and Communication Barriers to Trust of Israeli Patients in Acute-Care Physicians at Public General Hospitals

Abstract: Patient trust is positively related to health outcomes, but there remain barriers to patient trust in physicians. This narrative study analyzed patient experiences and highlights barriers to patient trust underlying communication with physicians in acute care. Snowball sampling was used. Informants were 12 participants, in poor physical health, upon discharge from a 3-week hospitalization in an acute-care setting at an Israeli public general hospital. Two narrative interviews were conducted with each participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…This study revealed needs and preferences of GPs during readmissions and the communication pathways that acute-care clinicians used to alleviate suffering, relate to distressing concerns of GPs and promote postdischarge resilience through comprehensibility, manageability and meaningfulness. When hospitalised in acute care, participants expected clinicians to address their distress (44,45). Several communication pathways that support Freire's theory of empowerment and Salutogenics, (14,15,22,23) fulfilled these expectations and promoted postdischarge resilience among participants.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed needs and preferences of GPs during readmissions and the communication pathways that acute-care clinicians used to alleviate suffering, relate to distressing concerns of GPs and promote postdischarge resilience through comprehensibility, manageability and meaningfulness. When hospitalised in acute care, participants expected clinicians to address their distress (44,45). Several communication pathways that support Freire's theory of empowerment and Salutogenics, (14,15,22,23) fulfilled these expectations and promoted postdischarge resilience among participants.…”
Section: Discussionmentioning
confidence: 99%
“…The impediments or barriers of communication mostly caused by the lack of intention [12,13], trust [14,15], interest [16], distraction [17,18] or irrelevance to the receiver [19,20]. Moreover, the differences in perceptions [21] and viewpoint [22] also has the potency to be the trigger.…”
Section: B Impediments To Communicationmentioning
confidence: 99%
“…Narrative communication messages either convey a point to another party or receive information from another party [31]. Narratives are a scientific way of relying on empirical and experimental methods to discover, describe, or elucidate some domain of interest through which we develop our understanding of the world and the distinctive ways of constructing reality [29,32]. One's engagement with a narrative may result in one's endorsement of modified attitudes and behaviors [33].…”
Section: The Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Prior studies that tested the effect of narrative persuasion, however, did not focus on health [35,36]. Narrative messages may be effective in the health-behavior context, as they are the basic mode of human interaction that we use in our day-to-day lives to influence others [32].…”
Section: The Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%